PENGEMBANGAN LKPD BERBASIS GUIDED DISCOVERY LEARNING BERBANTUAN GEOGEBRA UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH KELAS XI - Nina Murni Indriati; Siagian, Pargaulan (Koordinat Jurnal MIPA, 2024)
This research aims to develop LKPD based on guided discovery learning to improve students' problem solving abilities with the help of geogebra that is valid, practical and effective. This research uses research and development (R&D) research along with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The subjects of this research were 35 students in class XI-MIA 1 SMA Negeri 1 Batang Kuis. The research that has been carried out shows the results that the LKPD is in the valid category, seen from the results of expert validation of the LKPD reaching a percentage of 79%, the RPP reaching a percentage of 81% in the valid category, pre-test and post-test validation with a percentage of 88% and 91% which is classified as very valid. The LKPD was declared practical from the assessment of mathematics teachers and students through a response questionnaire with a percentage of 90% and 84% classified as very practical. The effectiveness of the LKPD is observed from the students' classical completion through the students' pre-test and post-test. There were 30 students who completed the test with a percentage of 86% and an increase in problem solving abilities as measured by the N-Gain calculation, namely with a value of 0.63, which is considered moderate. So that LKPD is effective in further improving students' problem solving abilities. So it can be concluded that the development of LKPD based on Geogebra-assisted Guided Discovery Learning fulfills all parameters in terms of increasing students' problem-solving abilities